Sport and Television: the role of the professional of Physical Education - Lopes da Silva, Cinthia; Avelaneda Origuela, Milena (FEADEF, 2012)
This paper has the objective of analyzing the relationship between sports and television, and identifies the role of the professional who acts in the field of Physical Education related to sport on television. The media institution produces discourses and an image related to sports and attributes a group of signifiers to this cultural element. Watching sport on television is different from watching them in a stadium or a gymnasium. This occurs because the televise production is restrict to the passes and scenes chosen previously by journalists and producers. As methodological procedures, it was made bibliographical review of qualitative type and also, thematic, textual, interpretative and critical analysis of the books written by scholars in the field of Leisure, Communication and Physical Education. The conclusions are: sport, when it is showed by television, it is transformed into entertainment. During this process, the role of the professional of Physical Education is essential to mediate knowledge. The teacher, based on the perspective of education for leisure, can help students to have access to the knowledge so they can reach superior and inventive level of comprehension. Accordingly, pedagogical mediation realized in formal education will be essential so that the subjects have access to theoretical elements for a qualified reading of the sport showed by media, thus, they can enjoy their moments of leisure with quality.